2020
DOI: 10.1051/e3sconf/202014502010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Environmental Benefits of Using low-Sulphur Oil and Shore Power Technology for Ship Berthing

Abstract: In order to compare the environmental benefits of two emission reduction measures, i.e. using low-sulphur oil and shore power technology, this paper takes the ships arriving at Guangzhou port as an example, based on the ship data of entry and departure visa of Guangzhou port in 2015, and uses statistical analysis to determine the relationship between different ship types of diesel engines, ship berthing time and ship deadweight tonnage, and based on the use of low-sulphur oil and berthing using shore power air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The main reason for investing in OPS refers to the environmental benefits that reduce noise, vibrations and emissions of pollution from ships when they are berthed. Hence, in databases there are numerous publications on this subject presenting environmental benefits of using OPS technology (Kizielewicz and Skrzeszewska, 2021;Sciberras et al, 2015;Saxena et al, 2012;Kumar et al, 2018;He et al, 2020;Wang et al, 2021b;Reusser and Pérez, 2021;Chen, 2022;Siu et al, 2022;Su et al, 2023) in particular in the area of CO 2 reduction potential of OPS (Stolz et al, 2021). The research carried out by Reusser and Pérez (2021) (Wang et al, 2021b) is a good example showing "the reduction in the specific fuel consumption of the auxiliary engines, thus reducing emissions in 20% for CO 2 , 34% for NO x and 30% for SO x " thanks to applying CI power configuration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for investing in OPS refers to the environmental benefits that reduce noise, vibrations and emissions of pollution from ships when they are berthed. Hence, in databases there are numerous publications on this subject presenting environmental benefits of using OPS technology (Kizielewicz and Skrzeszewska, 2021;Sciberras et al, 2015;Saxena et al, 2012;Kumar et al, 2018;He et al, 2020;Wang et al, 2021b;Reusser and Pérez, 2021;Chen, 2022;Siu et al, 2022;Su et al, 2023) in particular in the area of CO 2 reduction potential of OPS (Stolz et al, 2021). The research carried out by Reusser and Pérez (2021) (Wang et al, 2021b) is a good example showing "the reduction in the specific fuel consumption of the auxiliary engines, thus reducing emissions in 20% for CO 2 , 34% for NO x and 30% for SO x " thanks to applying CI power configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Reducing shipboard emissions Environmental Ben46efits of OPS Legal analysis (legal standards, law regulations, etc.) Regulation strategy for OPS Standardization in the Design of OPS Source: own elaboration on the base of: (IMO, 2015; Innes and Monios, 2018;IAPH, 2010;Winkel et al, 2016;Stolz et al, 2021;Bakar et al, 2022;Bullock et al, 2023;Hulme, 2006;AAPA, 2007;Haddadian and Haddadian, 2011;Acciaro et al, 2014;Qiong and Xiao, 2015;Sciberras et al, 2015;Yang and Chai, 2016;Atallah et al, 2017;Yu et al, 2017;Chengdi et al, 2018;He et al, 2018;Ji et al, 2018;Tarnapowicz and German-Galkin, 2018;Gutierrez-Romero et al, 2019;Kumar et al, 2019;Sun et al, 2019;Vlachokostas et al, 2019;Zis, 2019;Colarossi and Principi, 2020;He et al, 2020;Wang et al, 2020;Wang et al, 2021a;Jung and Schindler, 2021;Kizielewicz and Skrzeszewska, 2021;Martínez-Lopez et al, 2021;Ortiz-Imedio et al, 2021;Peng et al, 2021;Spengler and Tovar, 2021;Badakhshan et al, 2022;Farrukh et al, 2022;Galkin and Tarnapowicz, 2022;Karimi et al, 2022;Qiu et al, 2022;Williamsson et al, 2022;…”
Section: Author Contributionsmentioning
confidence: 99%
“…Some scholars taking Guangzhou Port as an example compared the environmental benefits of two emission reduction measures using low-sulfur oil and shore power technology. The results showed that shore power has significant advantages in reducing NO x emissions (He et al, 2020). In addition, quantitative calculations for Kaohsiung Port have shown the long-term potential of shore power to improve environmental and socioeconomic conditions by reducing port emissions (Tseng and Pilcher, 2015).…”
Section: Emission Reduction Effect Of Shore Powermentioning
confidence: 97%
“…The potential benefits of engine oil analysis extend to the prevention of costly repairs, reduction of downtime, and optimization of oil change intervals, resulting in early issue cost savings . Furthermore, issues contributing to increased emissions and contaminants leading to excessive exhaust emissions can be revealed through engine oil analysis, thereby offering environmental benefits . Despite the evident advantages of engine oil analysis, background research highlights a lack of definitive answers regarding the frequency at which it should be performed on diesel engines. , The frequency of engine oil analysis may necessitate adjustment as diesel engines age, requiring increased effort for reliability maintenance despite improving experience with aging.…”
Section: Introductionmentioning
confidence: 99%